Accrual Accounting – an Untapped Opportunity to Measure the Performance of Budgetary Bodies - Borbély, Tamás; Szikszainé Király, Mária; Kakas, Sándor (Public Finance Quarterly, 2021)
Hungary’s public accounting system underwent a significant reform in 2014. The reform meant not only a change in accounting, but also a new opportunity to support sustainable financial management and the measurement of organizational performance. In order to gather practical experience, a research was carried out by the State Audit Office of Hungary. In the areas selected during the research, based on the results of the survey, accrual-based accounting was only partially integrated into the accounting profit and return calculations of individual activities, and, especially in the case of smaller organizations, it did not exceed the mandatory, administrative role stipulated by law. Accrualbased accounting typically did not support the measurement of organizational performance. Further development can be carried out in terms of increasing the role of governing bodies in order to achieve target-setting, measurement and reporting along the same principles, as well as raising awareness. Moreover, in order to support organizational performance measurement, it may be necessary to develop a sectoral system of task and performance indicators, for which accrual-based accounting can become an important source of information.